Enhancing Medical Education Through Online Technologies: Investigating Adoption, Impact, and Optimization Strategies - Rahimi, Behnaz; Halimi, Yalda; Ghiasi, Zaynab; Afifi, Sara; Quraishi, Tamanna; Hakimi, Musawer (Educative: Jurnal Ilmiah Pendidikan, 2024)
Online technology' inclusion into medical education has transformed teaching strategies in recent years and offers fresh chances to improve learning environments and meet the changing needs of students and teachers. This study uses a thorough evaluation of the literature and empirical data to investigate, via online medical education, adoption, impact, and optimization tactics. The aim is to find important elements influencing their adoption, study the efficacy of online technologies in teaching medical topics, and suggest ways of best using them. Data was gathered from 120 people—including lecturers and students—across several departments of Rao University using a mixed-methods methodology. The results show notable good opinions on the usage of online learning technology; among medical teachers, Google Classroom is becoming the favored platform. Still, two main shortcomings were found to be technological problems and a lack of practical expertise. The findings lead to suggestions on how to make online medical education more effective: better access to materials, interactive learning settings, and addressing of communication restrictions among other things. All things considered, this study adds to the body of knowledge already in use by shedding light on the state of online medical education presently and by making doable suggestions for future expansion and application.